Insights Into the Role and Potential of Schwann Cells for Peripheral Nerve Repair From Studies of Development and Injury - Balakrishnan, Anjali; Belfiore, Lauren; Chu, Tak-Ho; Fleming, Taylor; Midha, Rajiv; Biernaskie, Jeff; Schuurmans, Carol (Frontiers in Molecular Neuroscience, 2021)
Peripheral nerve injuries arising from trauma or disease can lead to sensory and motor deficits and neuropathic pain. Despite the purported ability of the peripheral nerve to self-repair, lifelong disability is common. New molecular and cellular insights have begun to reveal why the peripheral nerve has limited repair capacity. The peripheral nerve is primarily comprised of axons and Schwann cells, the supporting glial cells that produce myelin to facilitate the rapid conduction of electrical impulses. Schwann cells are required for successful nerve regeneration; they partially ‘de-differentiate’ in response to injury, re-initiating the expression of developmental genes that support nerve repair. However, Schwann cell dysfunction, which occurs in chronic nerve injury, disease, and with aging, limits their capacity to support endogenous repair, worsening patient outcomes. Cell replacement-based therapeutic approaches using exogenous Schwann cells could be curative, but not all Schwann cells have a ‘repair’ phenotype, defined as the ability to promote axonal growth, maintain a proliferative phenotype and remyelinate axons. Two cell replacement strategies are being championed for peripheral nerve repair: prospective isolation of ‘repair’ Schwann cells for autologous cell transplants, which is hampered by supply challenges, and directed differentiation of pluripotent stem cells or lineage conversion of accessible somatic cells to induced Schwann cells, with the potential of ‘unlimited’ supply. All approaches require a solid understanding of the molecular mechanisms guiding Schwann cell development and the repair phenotype, which we review herein. Together these studies provide essential context for current efforts to design glial cell-based therapies for peripheral nerve regeneration.